Drug-induced reactivation of apoptosis abrogates HIV-1 infection. - Hartmut M Hanauske-Abel; Deepti Saxena; Paul E Palumbo; Axel-Rainer Hanauske; Augusto D Luchessi; Tavane D Cambiaghi; Mainul Hoque; Michael Spino; Darlene D'Alliessi Gandolfi; Debra S Heller; Sukhwinder Singh; Myung Hee Park; et al. (PLoS ONE, 2013)
HIV-1 blocks apoptosis, programmed cell death, an innate defense of cells against viral invasion. However, apoptosis can be selectively reactivated in HIV-infected cells by chemical agents that interfere with HIV-1 gene expression. We studied two globally used medicines, the topical antifungal ciclopirox and the iron chelator deferiprone, for their effect on apoptosis in HIV-infected H9 cells and in peripheral blood mononuclear cells infected with clinical HIV-1 isolates. Both medicines activated apoptosis preferentially in HIV-infected cells, suggesting that the drugs mediate escape from the viral suppression of defensive apoptosis. In infected H9 cells, ciclopirox and deferiprone enhanced mitochondrial membrane depolarization, initiating the intrinsic pathway of apoptosis to execution, as evidenced by caspase-3 activation, poly(ADP-ribose) polymerase proteolysis, DNA degradation, and apoptotic cell morphology. In isolate-infected peripheral blood mononuclear cells, ciclopirox collapsed HIV-1 production to the limit of viral protein and RNA detection. Despite prolonged monotherapy, ciclopirox did not elicit breakthrough. No viral re-emergence was observed even 12 weeks after drug cessation, suggesting elimination of the proviral reservoir. Tests in mice predictive for cytotoxicity to human epithelia did not detect tissue damage or activation of apoptosis at a ciclopirox concentration that exceeded by orders of magnitude the concentration causing death of infected cells. We infer that ciclopirox and deferiprone act via therapeutic reclamation of apoptotic proficiency (TRAP) in HIV-infected cells and trigger their preferential elimination. Perturbations in viral protein expression suggest that the antiretroviral activity of both drugs stems from their ability to inhibit hydroxylation of cellular proteins essential for apoptosis and for viral infection, exemplified by eIF5A. Our findings identify ciclopirox and deferiprone as prototypes of selectively cytocidal antivirals that eliminate viral infection by destroying infected cells. A drug-based drug discovery program, based on these compounds, is warranted to determine the potential of such agents in clinical trials of HIV-infected patients.